Svenska konsumenters attityd till potatis - Andersson, Lena (2008)
Until the sixties potatoes have had a unthreatened position at the Swedish dining tables, but then different alternatives such as rice and pasta have become popular. In 2005 the Swedish potato-consumption have more than hafted compared with the sixties, we have gone from circa 90 to 40 kilograms per person and year. This paper aims to provide those who are involved within the potatoe business with an overview of the attitude and behaviour towards potatoes that are being held by Swedish consumers. In order to reach to the conclusion, in- store interviews had been held with customers in the cities of Stockholm and Malmö. The interviews showed that the typical potato-consumer prefers to choose and in pick their own potatoes to a bag in the store in favour of the pre-packed alternatives. Based on the outcome of the interviews a number of conclusions could be drawn. The consumers were of the perception that the pre-packed alternatives were too big for their households. Furthermore the potato-business should gain from putting efforts to work with product differentiation and by that also provide the market with more exclusive alternatives.